A previdência social no Estado contemporâneo - Cardoso, Carina Kuhn (Universidade do Vale do Rio dos Sinos, 2019)
The research aims to verify the evolution of Brazilian Social Security, its configuration in the Contemporary State and, from this, to analyze its financing and viability, confronting the Brazilian Constitution of 1988 with the social security policies, situated within a framework of constitutional crisis, State crisis, and constraint of social rights by neoliberal ideologies. The first part of the research contextualized social protection considering the transformations of the State that led to the welfare state, which was a condition for the existence of a public pension, based on solidarity. However, the matter of social spending and the influences of neoliberalism have cast doubt on this model of state and social security. In the second part, the research focuses on the analysis of Brazilian Social Security, in order to demonstrate its origin, its evolution until the Constitution, and the processes of retraction that it has suffered because of successive reforms through constitutional and legislative changes. This work tries to demonstrate that the financing of Social Security was planned in detail in the Constitution to guarantee the costing of social security benefits and that there was already a large adjustment caused by the changes already made. In the last chapter, the research analyzes the supposed deficiency of the social security system in order to verify its consistency, especially considering that it is the main motto of the social security reform intended by Proposal of Constitutional Amendment nº 06/2019. Both the Government's discourse on the imminent bankruptcy of the social security system and, on the other hand, the studies demonstrating that pensions are sustainable were examined. The study analyzed how the economic and fiscal policies adopted in Brazil jeopardized social protection and served the interests of the privileged class in the social game. Finally, it demonstrated how the discussion about solidarity and the role of the State is involved with the issue of social security. The method of approach used for this research is the hermeneutic-phenomenological since it seeks to build an idea about the sustainability of social security in the Contemporary State. The research is bibliographical and documentary, developed from indirect documentation in primary sources, such as national legislation, statistics, and documents in general, as well as secondary bibliographic sources, such as in books and scientific journals. In the end, it was verified that the attacks on social security have as origin the neoliberal wave and the fiscal-financial crisis of the State, which is the reason to justify the reforms. However, although there is adequate funding for the payment of social security benefits, there is also mismanagement, misuse of resources, improper fiscal and economic policies that compromise the health of the social security system and serve the interests of a minority. Therefore, the payment of social security benefits cannot be considered responsible for the financial crisis of the State to justify restrictions on access to them. The reform sought by PEC No. 06/2019 is also a reform of the State and its role in social protection.
Keywords: Estado Social; Crise do Estado; Proteção social; Previdência Social; Reforma da Previdência; Social State; State Crisis; Social protection; Public Pension; Social Security Reform; ACCNPQ::Ciências Sociais Aplicadas::Direito